2022
DOI: 10.3847/2041-8213/ac69ca
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a 500 au Protobinary in the Massive Prestellar Core G11.92–0.61 MM2

Abstract: We present high-resolution (≲160 au) Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm observations of the high-mass prestellar core candidate G11.92−0.61 MM2, which reveal that this source is in fact a protobinary system with a projected separation of 505 au. The binary components, MM2E and MM2W, are compact (radii <140 au) sources within the partially optically thick dust emission with α 0.9 cm−1.3 mm = 2.47–2.94. The 1.3 mm brightness temperatures, T b = 68.4/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Several observations have revealed massive binary formation at the protostellar phase (e.g., Beltrán et al 2016;Tanaka et al 2020). Most recently, Cyganowski et al (2022) observed a (proto)binary in a massive core that was previously thought to be prestellar, making it one of the earliest-stage forming binaries that has the potential to become massive. Such observations put stringent constraints on massive binary formation theories (e.g., Krumholz et al 2009;Oliva & Kuiper 2020;Mignon-Risse et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several observations have revealed massive binary formation at the protostellar phase (e.g., Beltrán et al 2016;Tanaka et al 2020). Most recently, Cyganowski et al (2022) observed a (proto)binary in a massive core that was previously thought to be prestellar, making it one of the earliest-stage forming binaries that has the potential to become massive. Such observations put stringent constraints on massive binary formation theories (e.g., Krumholz et al 2009;Oliva & Kuiper 2020;Mignon-Risse et al 2021).…”
Section: Introductionmentioning
confidence: 99%